Epicardial adipose tissue volume highly correlates with left ventricular diastolic dysfunction in endogenous Cushing’s syndrome - Ran, Chun-Qiong; Su, Ying; Li, Jin; Wu, Kun; Liu, Zhe-Long; Yang, Yan; Zhang, Mu-Xun; Yuan, Gang; Yu, Xue-Feng; He, Wen-Tao (Annals of medicine (Helsinki), 2024)
Cushing's syndrome (CS) is associated with increased risk for heart failure, which often initially manifests as left ventricular diastolic dysfunction (LVDD). In this study, we aimed to explore the potential risk factors of LVDD in CS by incorporating body composition parameters. A retrospective study was conducted on patients diagnosed with endogenous CS no less than 18 years old. The control group consisted of healthy individuals who were matched to CS patients in terms of gender, age, and BMI. LIFEx software (version 7.3) was applied to measure epicardial adipose tissue volume (EATV) on non-contrast chest CT, as well as abdominal adipose tissue and skeletal muscle mass at the first lumbar vertebral level. Echocardiography was used to evaluate left ventricular (LV) diastolic function. Body compositions and clinical data were examined in relation to early LVDD. A total of 86 CS patients and 86 healthy controls were enrolled. EATV was significantly higher in CS patients compared to control subjects (150.33 cm [125.67, 189.41] vs 90.55 cm [66.80, 119.84], < 0.001). CS patients had noticeably increased visceral fat but decreased skeletal muscle in comparison to their healthy counterparts. Higher prevalence of LVDD was found in CS patients based on LV diastolic function evaluated by E/A ratio ( < 0.001). EATV was proved to be an independent risk factor for LVDD in CS patients (OR = 1.015, 95%CI 1.003-1.026, = 0.011). If the cut-point of EATV was set as 139.252 cm in CS patients, the diagnostic sensitivity and specificity of LVDD were 84.00% and 55.60%, respectively. CS was associated with marked accumulation of EAT and visceral fat, reduced skeletal muscle mass, and increased prevalence of LVDD. EATV was an independent risk factor for LVDD, suggesting the potential role of EAT in the development of LVDD in CS.